A diagnostic dilemma: a firm left submandibular node. (2nd December 2019) - Shabir, Aisha; Halai, Tina; Eyeson, Josiah
Abstract : A diagnostic conundrum of a firm, left submandibular node presenting in a 35-year-old female with a history of pain and persistent swelling is described. This paper aims to educate readers on the differential diagnostic dilemma that may be faced in general practice and discusses the importance of shared care in a multidisciplinary setting. CPD/Clinical Relevance: The presentation of this clinical case is discussed with radiographic imaging and the multidisciplinary approach undertaken for patient management. Readers can identify the steps undertaken in this case to exclude conditions in the surgical sieve.